Optimization of the Preventive Function of Lawyers in Divorce Mediation as an Effort to Resolve Family Disputes in Indonesia - Sofiatun Maemunatun; Obadiah Deoriesti Utomo; Saputri Wulandari; Devinia Devinia; Nur Rasdianto; Agatha Jumiati (Lembaga Pengembangan Kinerja Dosen, 2026)
The increase in national divorce rates based on data from the Central Statistics Agency in 2024, which reached 394,608 cases and rose to 438,168 cases in 2025, indicates that family conflicts remain a legal and social issue affecting family resilience, child protection, and social stability in society. In the Indonesian legal system, divorce is fundamentally placed as a last resort (ultimum remedium) after reconciliation thru mediation, as regulated in Law Number 1 of 1974 on Marriage, as amended by Law Number 16 of 2019, Supreme Court Regulation Number 1 of 2016 on Mediation Procedures in Court, and provisions in Law Number 18 of 2003 on Advocates. However, studies on the optimization of the preventive role of advocates in divorce mediation are still relatively limited, even tho advocates hold a strategic position as independent law enforcers within the judicial system. This research aims to analyze the legal position of lawyers in divorce mediation and to formulate the optimization of the lawyer's role in preventing avoidable divorces. The research uses a normative juridical method with legislative, conceptual, case, and comparative approaches thru the analysis of various related regulations, legal doctrines, and scientific literature. The research results show that lawyers not only function as legal representatives in litigation processes but also have a preventive role as legal advisors, negotiators, and facilitators of peaceful family dispute resolution. The optimization of these roles can be achieved thru the provision of objective legal advice, early identification of the root causes of family conflicts, facilitation of communication between parties, and collaboration with mediators and family counselors in the mediation process.